Amor and Venus Teach Music: Regarding Rubens’ Garden of Love - Piquer Sanclemente, Ruth (Eikón / Imago, 2018)
In the famous canvas The Garden of Love by Rubens (Museo del Prado), there are iconographic references that go beyond the representation of a court meeting, or, as main scholars have pointed out, the allusion to the painter’s recent marriage to Helena Fourment. The presence of a lute in the centre of the composition lead to a series of iconographic influences that make us think of the analogy between love and music, one of the most recurrent ideological and symbolic paradigms of the Modern Age, which had its main reference in the Amor docet musicam aphorism, embodied in numerous and different images of Dutch books of emblems and canvases. The notion ’Amor teaches music’ also responded to the social conventions on love and marriage that the Reformist and Catholic spheres spread among young people in the Netherlands. Considering this background I present a new perspective on this painting.